2015
DOI: 10.1152/jn.00060.2015
|View full text |Cite
|
Sign up to set email alerts
|

Reduced GABAergic inhibition and abnormal sensory symptoms in children with Tourette syndrome

Abstract: Tourette Syndrome (TS) is characterized by the presence of chronic tics. Individuals with TS often report difficulty with ignoring (habituating to) tactile sensations, and some patients perceive that this contributes to a "premonitory urge" to tic. While common, the physiological basis of impaired tactile processing in TS, and indeed tics themselves, remain poorly understood. It has been well established that GABAergic processing plays an important role in shaping the neurophysiological response to tactile sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 50 publications
5
73
5
Order By: Relevance
“…33 In an MRS study, it was shown that the GABA concentration in SM1 correlated negatively with motor tic severity. 53 Amphetamineinduced dopamin release in the ventral striatum was related to increased tic severity in one PET study, 61 while another PET study did not find any correlations between the TS-related metabolic covariance pattern (with increased activity bilaterally in premotor cortex and cerebellum, associated with relative reductions in striatum and orbitofrontal cortices) and severity of tics. 58 During voluntary movement control measured with MEG, larger amplitudes were inversely correlated with motor tic frequency and severity, 39 while another MEG study found ipsilateral motor cortical inhibition to be inversely related with tic severity.…”
Section: Neuroimaging and Severity Of Ticsmentioning
confidence: 97%
See 1 more Smart Citation
“…33 In an MRS study, it was shown that the GABA concentration in SM1 correlated negatively with motor tic severity. 53 Amphetamineinduced dopamin release in the ventral striatum was related to increased tic severity in one PET study, 61 while another PET study did not find any correlations between the TS-related metabolic covariance pattern (with increased activity bilaterally in premotor cortex and cerebellum, associated with relative reductions in striatum and orbitofrontal cortices) and severity of tics. 58 During voluntary movement control measured with MEG, larger amplitudes were inversely correlated with motor tic frequency and severity, 39 while another MEG study found ipsilateral motor cortical inhibition to be inversely related with tic severity.…”
Section: Neuroimaging and Severity Of Ticsmentioning
confidence: 97%
“…11,53 The GABA-ergic system is the main inhibitory system in the CNS, and GABA-ergic neurons are present in every brain structure. 54 Puts et al 53 found reduced primary sensorimotor cortex GABA concentrations in children with TS compared to control subjects. These findings suggest that reduced GABA concentrations in TS may contribute to both motor tics and sensory impairments in children with TS.…”
Section: Mrsmentioning
confidence: 99%
“…PET imaging of GABAA using [(11C)] flumazenil showed decreased binding bilaterally in the ventral striatum, globus pallidus, thalamus, amygdala and right insula 24 . In the cortex, a deficiency of inhibitory interneurons is suggested by a reduction of short-interval intracortical inhibition measured by transcranial magnetic stimulation and a reduction of GABA measured by 3T MRS in the primary sensorimotor cortex 25 . In contrast, 7T-MRS has shown elevated concentrations of GABA within the supplementary motor area 26 .…”
Section: Glutamatementioning
confidence: 99%
“…In TS, cortical GABAergic involvement is supported by transcranial magnetic stimulation measurements showing reduction of short-interval intra-cortical inhibition (Gilbert, 2006), MRS GABA findings in multiple cortical regions (Draper et al, 2014; Freed et al, 2016; Puts et al, 2015), and altered GABA A receptors quantified by [11C]flumazenil binding (Lerner et al, 2012). Evidence for striatal GABAergic involvement includes reduction of parvalbumin containing interneurons in postmortem human studies (Kataoka et al, 2010), and altered GABA A receptor binding (Lerner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, others (Puts et al, 2015) demonstrated TS related reductions in GABA in sensorimotor cortex among 8–12 year olds, with reductions predictive of motor tic severity. Similarly, among two published MRS studies of TS conducted at 7 T (using the LCModel fitting method), Draper et al (2014) reported increased GABA/NAA in supplemental motor cortex, but no changes in GABA/NAA in sensorimotor cortex among adolescents (mean age 15.7 ± 3 years); whereas Freed et al (2016) showed reduced GABA/water ratios in the anterior cingulate among teenagers with TS.…”
Section: Introductionmentioning
confidence: 99%